2020
DOI: 10.1088/2515-7620/ab7a77
|View full text |Cite
|
Sign up to set email alerts
|

Non-freezing cold event stresses can cause significant damage to mangrove seedlings: assessing the role of warming and nitrogen enrichment in a mesocosm study

Abstract: Mangroves are expanding poleward along coastlines globally as a response to rising temperatures and reduced incidence of freezing under climate change. Yet, knowledge of mangrove responses to infrequent cold events in the context of climate warming and regional nitrogen (N)-enriched eutrophication is limited. We conducted a mesocosm experiment in which the seedlings of two mangrove species (A. marina and B. gymnorrhiza) were grown either at ambient temperature or under warming with and without nitrogen (N) loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…There are a few studies conducted that demonstrate interspecific variation in the magnitude of reduction in photosynthesis, and activation of diverse photoprotection mechanisms in mangroves under cold (Zheng et al, 2016, 2016a; Chen et al, 2017; Song et al, 2020; Yan et al, 2021). For mangroves, we recently reported that along with multiple other photoprotection mechanisms, night respiration takes part in protecting thylakoid membrane damage to minimize the reduction of phytochemical efficiency and photoinhibition under cold (Yan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few studies conducted that demonstrate interspecific variation in the magnitude of reduction in photosynthesis, and activation of diverse photoprotection mechanisms in mangroves under cold (Zheng et al, 2016, 2016a; Chen et al, 2017; Song et al, 2020; Yan et al, 2021). For mangroves, we recently reported that along with multiple other photoprotection mechanisms, night respiration takes part in protecting thylakoid membrane damage to minimize the reduction of phytochemical efficiency and photoinhibition under cold (Yan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The development of mangroves in Qinzhou Bay over the past 3000 years showed that low air temperature causes mangrove degradation by impacting their diversity, productivity and area . It was also reported that cold event resulted in decreases in seedling growth rates and net ecosystem CO 2 uptake in mangroves (Song et al, 2020). However, most studies of mangrove stressors have focused on low air temperatures induced by extreme climate events; studies on low water temperatures induced by ocean currents are rare.…”
Section: Introductionmentioning
confidence: 99%